THE ENGLISH LEARNING MOTIVATION OF NURSING SCIENCE STUDENTS OF STIK BINA HUSADA PALEMBANG - Agus Wahyudi (Universitas Islam Ogan Komering Ilir Kayuagung, 2018)
Foreign language learning is closely related to human psychology, where learners or students are the centers of the learning process, their psychology is a key element in teaching and learning because affective factors such as motivation, it is the basis of linguistic factors such as learning or acquiring four language skills. The population of this study is the nursing science students of STIK Bina Husada in the 2017/2018 academic year; the sample of this study is the fourth-semester students who took English III subject, where there were 45 students consist of 15 males and 30 females. The purpose of this research was to find out the students’ English learning motivation of Nursing Science Students of STIK Bina Husada Palembang. The English learning motivation is categorized into a high, medium, and low the researcher used a motivation questionnaire to measure students’ motivation which consists of 40 structured questions (items) adapted from Ethel Ogane and Masako Sakamoto (1997). The result of this study showed that 21 (47%) students were in high motivation, 19 (42%) were in medium motivation, and 5 (11%) were in low motivation. Gardner (2006) posits that students with higher levels of motivation will do better than students with lower levels. He further adds that ‘if one is motivated, he/she has reasons (motives) for engaging in the relevant activities, expends effort, persists in the activities, attends to the tasks, shows the desire to achieve the goal, enjoys the activities, etc’